2015
DOI: 10.1039/c5ra05840f
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning of the hydrophobicity of caffeic acid: studies on the antimicrobial activity against Staphylococcus aureus and Escherichia coli

Abstract: The increased bacterial multidrug resistance caused by inappropriate use and overuse of antimicrobials is a global concern. To circumvent this issue, a quest for the development of new active agents has been widely recognized. Some phytochemical products, produced by plants as part of their chemical defense strategies, are regarded as new stimulus to develop novel antimicrobials that are not as vulnerable as current drugs to bacterial resistance mechanisms. In this study, the antimicrobial activity and mode of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 65 publications
(140 reference statements)
5
31
0
Order By: Relevance
“…In order to evaluate the influence of esterification on the HCAs' neurotrophic activity, a set of alkyl cinnamate derivatives based on p ‐coumaric acid, ferulic acid, sinapic acid, and caffeic acid were synthesized (Figure ). Short‐chain length alkyl esters were obtained following a microwave‐assisted Fischer esterification with the appropriate alcohol, as previously described (Scheme A) . Long‐chain alkyl ester derivatives were prepared by a Knoevenagel–Doebner condensation between the benzaldehyde with the appropriate aromatic pattern and the previously prepared malonate half ester with the desired tether length (Scheme B) The compounds were obtained in moderate to high yields and fully characterized by magnetic resonance spectroscopy ( 1 HRMN, 13 CRMN, and DEPT135) and mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the influence of esterification on the HCAs' neurotrophic activity, a set of alkyl cinnamate derivatives based on p ‐coumaric acid, ferulic acid, sinapic acid, and caffeic acid were synthesized (Figure ). Short‐chain length alkyl esters were obtained following a microwave‐assisted Fischer esterification with the appropriate alcohol, as previously described (Scheme A) . Long‐chain alkyl ester derivatives were prepared by a Knoevenagel–Doebner condensation between the benzaldehyde with the appropriate aromatic pattern and the previously prepared malonate half ester with the desired tether length (Scheme B) The compounds were obtained in moderate to high yields and fully characterized by magnetic resonance spectroscopy ( 1 HRMN, 13 CRMN, and DEPT135) and mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…The cinnamic acid (0.5 g), the appropriate alcohol (15 mmol), and two drops of concentrated sulfuric acid were added to a glass vial (2–5 mL) and sealed. The system was heated to 20 °C above the boiling point of the alcohol for 5 min . After cooling to room temperature, the crude product was purified by flash chromatography using silica gel as stationary phase and dichloromethane or ethyl acetate as eluent.…”
Section: Methodsmentioning
confidence: 99%
“…Ciprofloxacin (Sigma‐Aldrich) was used as positive control for MIC determination ( E. coli —0·25 μ g ml −1 ; S. aureus —0·5 μ g ml −1 ) (Andrade et al . ). The considered MIC values for C1, C2, C3 and C4 were the ones previously reported by Lopez‐Romero et al .…”
Section: Methodsmentioning
confidence: 97%
“…Negative controls were performed with cell suspensions with DMSO (10%, v/v) and bacterial cells without EO components. Ciprofloxacin (Sigma-Aldrich) was used as positive control for MIC determination (E. coli-0Á25 lg ml À1 ; S. aureus-0Á5 lg ml À1 ) (Andrade et al 2015). The considered MIC values for C1, C2, C3 and C4 were the ones previously reported by Lopez-Romero et al (2015).…”
Section: Determination Of Minimum Inhibitory Concentrationsmentioning
confidence: 99%
“…It was also observed that the longer side chains in the alkyl esters of caffeic acid showed better activity against Gram-positive bacteria, and the average chain length determined better activity against Gram-negative bacteria. The activity of the esters formed is directly related to lipophilicity, which affects the sensitivity of bacteria, the physicochemical properties of the bacteria and the integrity of cell membranes [ 129 ]. Generally, the structure of the cell wall of Gram-positive bacteria allows the penetration of hydrophobic molecules into the cell, while the membrane surrounding the wall of Gram-negative bacteria is virtually impermeable to them.…”
Section: Antimicrobial Properties Of Ncamentioning
confidence: 99%